2021
DOI: 10.1111/1365-2664.13830
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying crop pollinator dependence and its heterogeneity using multi‐level meta‐analysis

Abstract: Biotic pollination can benefit crop production, but its effects are highly variable. To maximise benefits from this ecosystem service, we need a greater understanding of the factors that cause variation so that ecological intensification can be more effectively applied. We focus on understanding the benefits of pollination to faba bean Vicia faba. We use a literature review followed by multi‐level meta‐analysis to estimate overall benefits of pollination to faba bean yield and to quantify variation (heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 79 publications
0
42
1
Order By: Relevance
“…This is likely due to nectar deprivation at the start of the study, which meant that B. terrestris shifted from robbing nectar to legitimate visit later in the season when there were less flowers open. The low frequency of legitimate flower visits could, explain why the decrease in bean weight per plant due to lack of pollination (15%) was modest when compared to results from a recent meta-analysis of faba bean pollinator dependency (37% on average, Bishop & Nakagawa, 2021) or an experiment using the same cultivar (Tiffany) and bumblebee hives (61%, Raderschall et al, 2021). In addition, a recent field study using the cultivar Tiffany, found no dependence on insect pollination , indicating high variation in pollination benefit within this cultivar, likely mediated by environmental conditions.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This is likely due to nectar deprivation at the start of the study, which meant that B. terrestris shifted from robbing nectar to legitimate visit later in the season when there were less flowers open. The low frequency of legitimate flower visits could, explain why the decrease in bean weight per plant due to lack of pollination (15%) was modest when compared to results from a recent meta-analysis of faba bean pollinator dependency (37% on average, Bishop & Nakagawa, 2021) or an experiment using the same cultivar (Tiffany) and bumblebee hives (61%, Raderschall et al, 2021). In addition, a recent field study using the cultivar Tiffany, found no dependence on insect pollination , indicating high variation in pollination benefit within this cultivar, likely mediated by environmental conditions.…”
Section: Discussionmentioning
confidence: 90%
“…Despite high variation between faba bean cultivars in their dependency on pollinators (Bishop et al, 2020;Bishop & Nakagawa, 2021), lack of insect pollination generally leads to lower yield in faba bean crops (Cunningham & Le Feuvre, 2013;Free & Williams, 1976;Raderschall et al, 2021;Riedel & Wort, 1960;Suso et al, 1996;Suso & del Río, 2015). This study confirms that lack of pollination decreases several faba bean yield components and is in line with a recent cage experiment using the same cultivar (Tiffany), where bean weight per plant and beans per pod but not individual bean weight benefitted from insect pollination (Raderschall et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 50 years, faba bean cropping area has been declining due to yield instabilities, associated to abiotic stress, pest and pathogen pressure (Karkanis et al, 2018 ), and possibly uneven insect pollination. Faba beans are partially dependent on insect pollinators (Bishop & Nakagawa, 2021 ), with honeybees and bumblebees being the dominant pollinators in Northern Europe (Nayak et al, 2015 ; Raderschall et al, 2021 ). While insect pollination generally increases faba bean yield and yield stability (Suso & Maalouf, 2010 ; Suso & del Río, 2015 ), pollination dependence within cultivars varies greatly, from −4 to 46% (loss in yield per plant without pollination) (Bishop et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Faba bean is pollinated by wild and domestic bees. Without bee pollination, the yield is decreased by more than 30% (Bishop and Nakagawa 2021 ). Both self-pollen and cross-pollen are fertile and fully compatible (Link and Ghaouti 2012 ).…”
Section: Introductionmentioning
confidence: 99%